Analisis Pelaksanaan Alih Media Rekam Medis Rawat Inap di Rumah Sakit X - Ade Irma Suryani; Aqil Bintang Nugroho (Jurnal Infokes, 2026)
One of the important stages in implementing Electronic Medical Records (RME), which has been mandatory since 2024, is the process of transferring medical record media from physical format to electronic format. The purpose of this study is to understand the implementation of inpatient medical record media transfer at Hospital X, as well as analyze the obstacles faced during the process. This study used a qualitative method with a descriptive approach, direct observation and in-depth interviews with five medical record officers were used as data collection techniques in this qualitative study. The results showed that, since the beginning of implementation in June 2023 until February 2025, only 37% of 71,705 inpatient medical records had been converted to electronic format. Based on the analysis of the 5M elements (Man, Money, Method, Machine, and Material), several obstacles were found in the implementation of media transfer, namely the shortage of medical record officers, limited budget for device provision and maintenance, SOPs that have not been updated, inconsistent device performance, and damage to medical records during the scanning process due to the use of staplers. To support the overall success of the media transfer process, the hospital should immediately increase the number of medical record officers, make a special budget plan, evaluate and improve SOPs, upgrade supporting devices, and check medical records before scanning.